2018
DOI: 10.5603/gp.a2018.0106
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the influence of infection on overall survival rates, following modified posterior pelvic exenteration for advanced ovarian cancer

Abstract: Objectives:The aim of our study was to determine the association between the appearance of infection after modified posterior pelvic exenteration (MPE) and the time to adjuvant chemotherapy (TTC), and to examine whether infection has any impact on clinical results by delaying the start of chemotherapy. Material and methods:Our retrospective study analyzed 77 patients who had undergone MPE followed by adjuvant chemotherapy. Postoperatively, either there was no residual tumor or, the residual tumor was less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Cancer surgery is necessary and life-saving; however, the majority of patients develop postoperative recurrence and metastases, which constitute the main causes of cancer-related deaths [32]. Rationally combining cancer surgery with immunotherapies can transform the immunosuppressive effect into a therapeutic opportunity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer surgery is necessary and life-saving; however, the majority of patients develop postoperative recurrence and metastases, which constitute the main causes of cancer-related deaths [32]. Rationally combining cancer surgery with immunotherapies can transform the immunosuppressive effect into a therapeutic opportunity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that tumor RCAS1 expression is an indicator of poor prognoses in patients with cancer [16,[24][25][26][27][28][29]. However, there is sparse data on serum sRCAS1 levels as a prognostic factor in human malignancies, and most of the data that does exist relates to the evaluation of short term outcomes [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is sparse data on serum sRCAS1 levels as a prognostic factor in human malignancies, and most of the data that does exist relates to the evaluation of short term outcomes [23]. From a clinical point of view, the most informative prognostic factors are those that influence patients' overall survival (OS) [28,30]. To the best of our knowledge, there is no study evaluating the influence of serum sRCAS1 levels on the OS rates of patients with endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies evaluated predominantly short-term outcomes or correlated sRCAS1 levels with other prognostic factors. 7,26,27 The main result of our study indicates the prognostic utility of serum sRCAS1 levels in patients with cervical cancer. We have shown that increased levels of posttreatment serum sRCAS1 were associated with shortened OS.…”
Section: Discussionmentioning
confidence: 55%
“…Only a few studies have focused on the prognostic significance of serum sRCAS1 levels in human neoplasms. However, these studies evaluated predominantly short‐term outcomes or correlated sRCAS1 levels with other prognostic factors . The main result of our study indicates the prognostic utility of serum sRCAS1 levels in patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 72%